Case Report: Adrenal angiomatoid fibrous histiocytoma misdiagnosed as pheochromocytoma - Yao, Ziyou; Peng, Yinqi; Bi, Xianze; Chen, Wenyuan; Wang, Bo; Zhang, Jiange; Huang, Haipeng (Frontiers in Oncology, 2025)
BackgroundAdrenal angiomatoid fibrous histiocytoma (AFH) is a rare soft tissue tumor that is frequently misdiagnosed preoperatively. This diagnostic challenge is compounded by its nonspecific clinical presentation and radiological features, which often overlap with more common adrenal neoplasms such as pheochromocytoma, adrenocortical carcinoma, and metastasis. This report describes a case of adrenal AFH that was successfully managed via retroperitoneal laparoscopic adrenalectomy.Case introductionAn 18-year-old male presented with a two-week history of recurrent abdominal pain and vomiting. Preoperative computed tomography angiography and urography suggested a pheochromocytoma. Pheochromocytoma was initially suspected based on preoperative computed tomography angiography and urography findings; however, postoperative pathological analysis confirmed the diagnosis as adrenal angiomatoid fibrous histiocytoma. There was no recurrence of adrenal angiomatoid fibrous histiocytoma during the follow-up of 10 months.ConclusionsAdrenal AFH is a rare tumor with a high propensity for misdiagnosis. It should be considered in the differential diagnosis of adrenal masses with imaging features suggestive of hemangioma. Surgical resection is the primary treatment, and the prognosis is generally favorable without the need for adjuvant radiotherapy or chemotherapy. Long-term surveillance is recommended due to its intermediate biological potential and documented risk of late recurrence.